Switchable highly regioselective synthesis of 3,4-dihydroquinoxalin-2(1H)ones from o-phenylenediamines and aroylpyruvates - Dobiaš, Juraj; Ondruš, Marek; Addová, Gabriela; Boháč, Andrej (Beilstein Journal of Organic Chemistry, 2017)
3-Acylmethylidene-3,4-dihydroquinoxalin-2(1H)-ones are compounds which possess a wide range of physical and pharmaceutical applications. These compounds can be easily prepared by cyclocondensation of o-phenylenediamines and aroylpyruvates. Unsymmetrically substituted o-phenylenediamines can be obtained form regioisomeric mixtures of 3,4-dihydroquinoxalin-2(1H)-ones. It is often quite difficult to get a pure regioisomer and determine its structure without controlling the reaction selectivity and exploitation of complex NMR techniques (HSQC, NOESY, HMBC). This article examines the regioselectivity of the cyclocondensation between six monosubstituted o-phenylenediamines (-OMe, -F, -Cl, -COOH, -CN, -NO2) and the derivatives of p-chlorobenzoylpyruvate (ester or acid) which we studied. Six regioisomeric 3,4-dihydroquinoxalin-2(1H)-one pairs were selectively prepared and characterised. Based on our experiences, a simplified methodology for determining the structure of the regioisomers was proposed. We developed two general and highly selective methodologies starting from the same o-phenylenediamines and activated 4-chlorobenzoylpyruvates (ester or acid) enabling switching of 3,4-dihydroquinoxalin-2(1H)-one regioselectivity in a predictable manner. For comparison, all regioselective cyclocondensations were performed with the same standardized conditions (DMF, rt, 3 days), differing only by the additives p-TsOH or HOBt/DIC (hydroxybenzotriazole/N,N’-diisopropylcarbodiimide). Both selected methods are simple, general and highly regioselective (72–97%). A mechanism for the regioselectivity was also proposed and discussed. This study can be used as a guide when choosing the most optimal reaction conditions for the synthesis of the desired 3,4-dihydroquinoxalin-2(1H)-one regioisomers with the best selectivity. The demonstrated methodologies in this article may also be applied to differently substituted 3,4-dihydroquinoxalin-2(1H)-ones in general, which could expand the synthetic impact of our results.
Keywords: controlled regioselectivity; cyclocondensation; 3,4-dihydroquinoxaline-2(1H)one; HOBt/DIC; mechanism

(untitled) - Qin, X.; Hao, X.; Han, H.; Zhu, S.; Yang, Y.; Wu, B.; Hussain, S.; Parveen, S.; Jing, C.; Ma, B.; Zhu, C. (J. Med. Chem., 2015)

(untitled) - Carta, A.; Piras, S.; Loriga, G.; Paglietti, G. (Mini-Rev. Med. Chem., 2006)

(untitled) - Abu-Hashem, A. A. (Am. J. Org. Chem., 2015)

(untitled) - Kurasawa, Y.; Miyashita, R.; Takada, A.; Kim, H. S.; Okamoto, Y. (J. Heterocycl. Chem., 1995)

(untitled) - Seki, T.; Iwanami, Y.; Kuwatani, Y.; Iyoda, M. (J. Heterocycl. Chem., 1997)

(untitled) - Xu, Y.-S.; Zeng, C.-C.; Li, X.-M.; Zhong, R.-G.; Zeng, Y. (Chin. J. Chem., 2006)

(untitled) - Badawy, M. A.; Mohamed, G. G.; Omar, M. M.; Nassar, M. M.; Kamel, A. B. (Eur. J. Chem., 2010)

(untitled) - Korin, E.; Cohen, B.; Liu, Y.-D.; Zeng, C.-C.; Shames, A. I.; Becker, J. Y. (J. Coord. Chem., 2013)

(untitled) - Xia, M.; Wu, B.; Xiang, G. (J. Fluorine Chem., 2008)

(untitled) - Yao, Q.-C.; Wu, D.-E.; Ma, R.-Z.; Xia, M. (J. Organomet. Chem., 2013)

(untitled) - Mashevskaya, I. V.; Tolmacheva, I. A.; Voronova, E. V.; Odegova, T. F.; Aleksandrova, G. A.; Goleneva, A. F.; Kol’tsova, S. V.; Maslivets, A. N. (Khim.-Farm. Zh., 2002)

(untitled) - Ambaye, N. D.; Gunzburg, M. J.; Lim, R. C. C.; Price, J. T.; Wilce, M. C. J.; Wilce, J. A. (Bioorg. Med. Chem., 2011)

(untitled) - Ciustea, M.; Silverman, J. E. Y.; Druck Shudofsky, A. M.; Ricciardi, R. P. (J. Med. Chem., 2008)

(untitled) - Drwal, M. N.; Marinello, J.; Manzo, S. G.; Wakelin, L. P. G.; Capranico, G.; Griffith, R. (PLoS One, 2014)

(untitled) - Fan, C.; Clay, M. D.; Deyholos, M. K.; Vederas, J. C. (Bioorg. Med. Chem., 2010)

(untitled) - Habash, M.; Abdelazeem, A. H.; Taha, M. O. (Med. Chem. Res., 2014)

(untitled) - Krueger, B. A.; Weil, T.; Schneider, G. (J. Comput.-Aided Mol. Des., 2009)

(untitled) - Park, H.; Jung, S.-K.; Yu, K. R.; Kim, J. H.; Kim, Y.-S.; Ko, J. H.; Park, B. C.; Kim, S. J. (Chem. Biol. Drug Des., 2011)

(untitled) - Taha, M. O.; Atallah, N.; Al-Bakri, A. G.; Paradis-Bleau, C.; Zalloum, H.; Younis, K. S.; Levesque, R. C. (Bioorg. Med. Chem., 2008)

(untitled) - Tayyem, R. F.; Zalloum, H. M.; Elmaghrabi, M. R.; Yousef, A.-M.; Mubarak, M. S. (Eur. J. Med. Chem., 2012)

(untitled) - Sanna, P.; Carta, A.; Loriga, M.; Zanetti, S.; Sechi, L. (Farmaco, 1999)

(untitled) - Korin, E.; Cohen, B.; Bai, Y.-X.; Zeng, C.-C.; Becker, J. Y. (Tetrahedron, 2012)

(untitled) - Andreichikov, Y. S.; Nekrasov, D. D.; Pitirimova, S. G.; Zaks, A. S.; Korsheninnikova, M. I.; Plaksina, P. N.; Semenova, Z. N.; Kopeikin, V. A. (Khim.-Farm. Zh., 1989)

(untitled) - Abasolo, M. I.; Gaozza, C. H.; Fernández, B. M. (J. Heterocycl. Chem., 1987)

(untitled) - Mondieig, D.; Negrier, P.; Massip, S.; Leger, J. M.; Jarmoumi, C.; Lakhrissi, B. (J. Phys. Org. Chem., 2011)

(untitled) - Xia, Q.-H.; Hu, W.; Li, C.; Wu, J.-F.; Yang, L.; Han, X.-M.; Shen, Y.-M.; Li, Z.-Y.; Li, X. (Eur. J. Med. Chem., 2016)

(untitled) - Sherman, D.; Kawakami, J.; He, H.-Y.; Dhun, F.; Rios, R.; Liu, H.; Pan, W.; Xu, Y.-J.; Hong, S.-p.; Arbour, M.; Labelle, M.; Duncton, M. A. J. (Tetrahedron Lett., 2007)

(untitled) - Sakata, G.; Makino, K.; Morimoto, K. (Heterocycles, 1985)

(untitled) - Cushing, T. D.; Hao, X.; Shin, Y.; Andrews, K.; Brown, M.; Cardozo, M.; Chen, Y.; Duquette, J.; Fisher, B.; Gonzalez-Lopez de Turiso, F.; He, X.; Henne, K. R.; et al. (J. Med. Chem., 2015)

(untitled) - Liu, R.; Huang, Z.; Murray, M. G.; Guo, X.; Liu, G. (J. Med. Chem., 2011)

(untitled) - Kher, S. M.; Cai, S. X.; Weber, E.; Keana, J. F. W. (J. Org. Chem., 1995)